Comparison of Ibuprofen with Ketorolac on the Control of Renal Colic Pain: A Meta-Analysis of Randomized Controlled Studies - Cai, Fuxian; Liao, Yougang; Jiang, Shichun; Cao, Yuan; Wang, Yaodong (Urology Journal, 2023)
Purpose: The comparison of ibuprofen with ketorolac remains controversial for the pain control of renal colic. We therefore conduct this meta-analysis to compare the analgesic efficacy of ibuprofen with ketorolac for renal colic. Methods: We have searched PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases through December 2022 for randomized controlled trials (RCTs) assessing the analgesic efficacy of ibuprofen in comparison with ketorolac for renal colic. This meta-analysis was performed using the random-effect or fixed-effect model based on the heterogeneity. Results: Four RCTs were included in the meta-analysis. In patients with renal colic pain, intravenous ibuprofen and ketorolac produced comparable pain scores at 15 min (MD = -0.46; 95% CI = -1.24 to 0.31; P = 0.24), 30 min (MD = -0.81; 95% CI = -1.75 to 0.31; P = 0.09), 60 min (MD=-0.63; 95% CI = -1.40 to 0.13; P = 0.10) and 120 min (MD = -0.74; 95% CI = -2.18 to 0.70; P = 0.31), as well as adverse events (OR = 0.95; 95% CI = 0.61 to 1.49; P = 0.83). Conclusion: Ibuprofen can obtain comparable analgesic efficacy to ketorolac for renal colic pain.